Pausanias: a perieget in Second Sophistic? - Ramos da Silva, Arhão Henrique (Romanitas - Revista de Estudos Grecolatinos, 2026)
The Description of Greece, written by Pausanias in the 2nd century AD, is a work composed of ten Books that detail the regions of continental Greece, combining geographical, historical and cultural descriptions. The author emphasizes monuments, religious rituals and local traditions, in addition to reporting conflicts and political events, such as Roman domination. The article analyzes this work within the context of the Second Sophistic, highlighting its archaizing character and its relationship with cultural memory and Greek identity, as discussed by Bommas (2011) and Alcock (1996). It is argued that the Description of Greece responds to the provincialization of Greece after 146 BC, reflecting both an idealized glorious past and the adaptation to Roman rule. While Porter (2001) and Pretzler (2007) emphasize its performative and informative character, Habicht (1998) criticizes the intellectual superficiality of the period. Anderson (1993) and Whitmarsh (2005) emphasize the construction of Greek identity under Rome. The study also relates Pausanias to sophists such as Polemus and Aelius Aristides, demonstrating how his work is inserted in a hybrid political and cultural context, where rhetoric and erudition supported both entertainment and the affirmation of Greek identity, highlighting the effervescent intellectual panorama of the period.